Educational Thought of Hasan Langgulung - Munasti, Holida; Gulo, Kamil; Hanum, Azizah (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2024)
This study examines the educational thought of Hasan Langgulung, a significant figure in contemporary Islamic education. Through an analysis of Langgulung's works and writings, this research explores the main principles shaping his educational views. The study employs a qualitative approach using content analysis, where Langgulung's works are read and analyzed in depth to identify key themes such as the integration of science and religion, a holistic approach to education, and the importance of comprehensive individual development. Data validation is achieved through triangulation by comparing the analysis results with the perspectives of other experts in secondary literature and consulting academics with expertise in Islamic education. The findings of this research are expected to provide deep insights into Hasan Langgulung's contributions to educational theory and practice, and offer valuable perspectives for the development of a more integrative and holistic educational system.